IMPLEMENTATION OF SHARIA TOURISM ACCOMMODATION AT THE KRIYAD MURAYA HOTEL BANDA ACEH - Putra, Muhammad Rizki Mahalian; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Hotels include business ventures that emphasize service sales. A sharia hotel is a hotel that implements a sharia system in a hotel which affects the way it is managed, the type of hotel, the hotel classification, to the sharia-compliant waste treatment. One of the activities carried out by sharia hotels is to attract customers in various ways without leaving the context of the sharia. Without this kind of implementation efforts to increase room sales are very difficult because many guests are still afraid to stay at Islamic hotels based on the principle of "Privacy". This is what makes the general public still confused about what is called a sharia hotel. This study aims to determine how the responses of local and foreign tourists regarding the implementation of sharia hotel provisions in all Aceh Province. This study uses a quantitative method with a descriptive approach in which the research will take data from informants to find out how the responses of tourists staying at hotels in Aceh Province. While the data collection in this study used observation, questionnaires, interviews, and documentation. From the research results, an indicator is knowing how the satisfaction of tourists staying at hotels in Aceh Province, especially in the city of Banda Aceh and also to be a reference in the future regarding tourist responses that can be a consideration for other hotels throughout Indonesia. Keywords: Sharia hotels, Sharia, Tourist response